Ponatinib Tyrosine Kinase Inhibitor Induces a Thromboinflammatory Response - Hamadi, Abdullah; Grigg, Andrew P.; Dobie, Gasim; Burbury, Kate L.; Schwarer, Anthony P.; Kwa, Faith A.; Jackson, Denise E. (Thrombosis and Haemostasis, 2019)
Both nilotinib, a second-generation tyrosine kinase inhibitor (TKI) used in the treatment of chronic myeloid leukaemia (CML), and ponatinib, a third-generation TKI used in CML and Philadelphia positive acute lymphocytic leukaemia, have been associated with an increase in arterial occlusive events, in contrast to other TKIs such as imatinib and dasatinib. We have previously demonstrated evidence of a pro-thrombotic state associated with nilotinib, using microvascular and arterial thrombosis C57BL/6 mouse models. In this study, we examined ponatinib and determined if a calcium channel blocker could ameliorate the pro-thrombotic and pro-inflammatory phenotypes. In vitro treatment of whole human or murine blood with ponatinib and nilotinib increased platelet activation, adhesion and three-dimensional thrombi over time compared with vehicle control or other TKIs. Treatment of wild-type C57BL/6 mice with ponatinib and nilotinib but not imatinib, dasatinib or vehicle control for 4 hours significantly increased thrombus growth following ex vivo perfusion on collagen and FeCl3-induced vascular injury of mesenteric arterioles and carotid artery in vivo and increased plasma levels of soluble P-selectin, tumour necrosis factor-α, interleukin-6, interferon-γ and thromboxane B2 (TxB2). Ponatinib-treated CML patients had increased ex vivo thrombus formation and a pro-inflammatory phenotype compared with healthy controls. Pre-treatment of mice with the calcium channel antagonist, diltiazem, prior to ponatinib or nilotinib reversed the pro-thrombotic phenotype and the increase in cytokine levels. These observations suggest that the pro-thrombotic effect of nilotinib and ponatinib is partially related to calcium channel activation and TxA2 generation and this should be explored clinically as a mechanism to prevent vascular events.
Keywords: calcium channel blocker; nilotinib; ponatinib; pro-thrombotic; tyrosine kinase inhibitor; thromboxane A2